Perceptions and preparedness toward tobacco cessation counseling amongst clinical medical students in Chongqing, Southwest China: A cross-sectional study - Yang, Chuang; He, Wenjin; Deng, Ruihang; Giri, Mohan; Dai, Haiyun (Frontiers in Public Health, 2022)
Background Medical students play an indispensable role in providing smoking cessation counseling. Despite the rapid increase in tobacco use, there is little data on what Chinese medical students know or are taught about it. This study aims to investigate the relationship between medical students' tobacco education level, clinical experience, and tobacco cessation counseling (TCC) provided by medical students. Methods This cross-sectional study was carried out among clinical medical students of Chongqing medical university. An anonymous, self-administered questionnaire included items on demographic information, perceptions, and perceived preparedness, clinical medical students’ self-reported level of education about alternative tobacco products, and traditional cigarettes. We assessed their perspectives toward TCC using a 5-point Likert scale. Descriptive and binary logistic regression analyses were carried out. Results A total of 1,263 medical students completed the questionnaire. The majority of students (85%) expressed a willingness to provide TCC to patients in need. However, only half of the students stated unequivocally that they knew some ways and methods of tobacco cessation, while 18% stated that they did not know methods of tobacco cessation. Tobacco education and clinical experience were significantly associated with the ability to provide TCC. Our findings revealed that students with more clinical experience (undergraduates: B = 0.326, P<0.001; postgraduates: B = 0.518, P<0.001) were significantly more likely to have a greater self-reported comprehensive ability to provide TCC. Conclusion Tobacco education and clinical experience can enhance the ability of medical students to provide smoking cessation counseling. There is a need to focus on alternative tobacco products with changing times, and curriculum planners should collaborate to incorporate comprehensive tobacco prevention and cessation training into the medical school curriculum.